(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the phenomenon of synonymy and variation in the investigated lexics. Also stylistic potential of positive and negative marking lexems is cleared up.